The water line : research into the peculiar place of the Namib Desert coast - Pineo, Sarah (School of Architecture, Planning and Geomatics, 2015)
This dissertation began as a study of a portion of the coastal Namib Desert that I am particularly inspired by and with which I formed a personal connection over the course of many childhood coastal excursions. From these studies a site within the salt pan mine concession outside of Swakopmund was chosen. Stretching from the ocean to the edge of an existing naturalindustrial salt pan, this site becomes the location for my architectural intervention, the Water Line. This intervention is a testing space for a small scale solar desalination and fog catching system that services a hydrology research center base, as well as attempting to incorporate a more public exposure to this form of technology and the water resource potential it provides. Before design within this landscape could be considered, both a more poetic and pragmatic understanding of this peculiar place and its extreme conditions was necessary. In considering the landscape and celebrating the natural-human idiosyncrasies of this particular landscape, and a specific site within it, the hope of invoking and advocating for the singularity of local phenomena is attempted through design. Throughout this dissertation the understanding of context and character of place was viewed as a means by which the architectural possibilities of the intricacies, peculiarities and experience of a space and landscape could be questioned. It was, and remains, a journey of discovery and understanding of place. The intention of this document is to highlight the many aspects of the environment; from historical, human and biological interrogations to its experiential and functional clues. Understanding context and landscape through multiple layers and scales is vital in this space of eternal contrasts. It is in a sense the only way to obtain a greater understanding of "sitedness" of this project. The existing responses to environment and place-making within this context also provide clues to how to capture a unique response to the singularities of this space, without succumbing to the ease of uniformity. Within this understanding is the theoretical questioning of what the architecture of this space could become.